Poverty in the EU using augmented measures of financial resources: The role of assets and debt. (December 2021) - Kuypers, Sarah; Marx, Ive
Despite clear limitations, poverty research in the rich world overwhelmingly relies on income-based measures. Households may have significant savings and assets that they can draw on to boost their living standards, but may also have debts that depress the living standard they can actually achieve with their disposable income. Using data from the Eurosystem Household Finance and Consumption Survey (HFCS), this article offers a picture of poverty in 17 EU countries that takes into account assets and debt, using various approaches. While earlier studies have found that poverty rates tend to be lower when wealth is accounted for, this study highlights the situation of those who become or remain poor even when savings and assets are included. It focuses both on within-country patterns of joint income–wealth poverty and on cross-country differences. It is shown that the elderly are generally less prone to being poor once assets are accounted for. However, for renter households with a young, female, low educated, unemployed or inactive and single head, the risk of being poor when assets and debt are accounted for remains high and in some cases even increases. That is generally the case because they have few assets, rather than because of high debts. The substantial variation in poverty rates observed across countries can to some extent be accounted for by socio-demographic factors, but a lot of variation still remains unaccounted for.